COMPARATIVE CHARACTERISTICS OF MORPHOMETRIC PARAMETERS IN RIGHT-HANDED AND LEFT-HANDED CHILDREN OF THE II PERIOD OF CHILDHOOD - Rustamova N. B. (Academia Science Repository, 2023)
The analysis was carried out on 10-year-old children of secondary schools No. 7. The results of the study showed that 10-year-old left-handed children lagged somewhat in physical development (body weight and chest circumference) compared with right-handed children of the same age, while the height and size of the left arm significantly increased.